Rekayasa Ulang Metode Pekerjaan Pengecoran dan Bekisting untuk Meningkatkan Kinerja Waktu dan Biaya Proyek Gedung Bertingkat - Dedi Achyadi; Kartono Wibowo; Soedarsono Soedarsono (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
Time delays and cost overruns remain major problems in building construction projects, particularly in concrete structural works that dominate project duration and cost. This study aims to evaluate the application of re-engineering in concrete structural work methods on the time and cost performance of multi-storey building projects. A quantitative approach using a case study method was employed through comparative analysis between the existing method and alternative methods. The analyzed alternatives include ready-mix concrete with Sika Viscocrete 8007 admixture and semi-system formwork as Alternative I, ready-mix concrete with system formwork as Alternative II, and ready-mix concrete with Sika Viscocrete 8007 admixture combined with system formwork as Alternative III. The results show that all alternatives perform better than the existing method with a duration of 243 days. Alternative I reduced the duration to 208 days with cost efficiency of IDR 55,781,730 or 0.214 percent. Alternative II reduced the duration to 203 days with cost efficiency of IDR 187,553,261 or 0.724 percent. Alternative III achieved the best performance with a duration of 168 days, accelerating 75 days and providing the highest cost efficiency of IDR 243,334,991 or 0.941 percent. The study concludes that re-engineering effectively improves project time and cost performance, with Alternative III as the optimal method.